Interlinked patterns in movements and otolith formation of cod (Gadus morhua) in the southern Baltic Sea - Haase, Stefanie (2021)
Some of the best studied fish species with the longest monitored stock time series worldwide occur in the North Atlantic. Over the decades numerous publications added knowledge to our understanding of ecology and behaviour of these fish species and stocks. However, there are also gaps in knowledge, obvious uncertainties in ecological interactions and potential biases. These are rarely profoundly questioned unless environmental changes or inconsistent stock assessment results challenge our established points of view. In the Baltic Sea, Atlantic cod (Gadus morhua L.) has been intensively surveyed and investigated for decades. Yet, our understanding of this marine species living in a semi-enclosed, brackish environment is still incomplete. For example, despite numerous otolith exchanges to improve the age reading and large scientific efforts to understand the ecology of Baltic cod, the analytical stock assessment of the Eastern Baltic cod (EBC) stock was suspended in 2014; obviously age data were uncertain and the aut- and synecological knowledge was incomplete to explain the changes occurring in this stock in distress. For instance, spreading hypoxic areas in the central Baltic basins forced EBC to contract in the southern Baltic Sea but behaviour and movements of cod in response to the consequences are poorly understood. This dissertation aims at providing a more thorough understanding of cod ecology in the southern Baltic Sea, with a particular focus on patterns in movements of wild, free-ranging cod and validation of ring patterns in otoliths. Tagging performance, data storage tags recording depth and ambient temperature and otoliths of recaptured cod were analysed. Tagged cod had been released in the southern Baltic Sea within the scope of the international mark-recapture project TABACOD (“Tagging Baltic cod”). In chapter 1 (“Short-term tagging mortality of Baltic cod (Gadus morhua)”) the post-release short-term mortality of cod after tagging with T-bar tags and tetracycline was assessed. The mortality ...